MOVING STONE IN THE HELE-SHAW FLOW. Issue 2 (8th April 2015) - Mishuris, Gennady; Rogosin, Sergei; Wrobel, Michal
Abstract : Asymptotic analysis of the Hele-Shaw flow with a small moving obstacle is performed. The method of solution utilizes the uniform asymptotic formulas for Green's and Neumann functions recently obtained by V. Maz'ya and A. Movchan. The theoretical results of the paper are illustrated by numerical simulations.